Nutritional literacy and its influence on healthy lifestyle behavior and willingness to consume healthy food brands - García-Salirrosas, Elizabeth Emperatriz; Escobar-Farfán, Manuel; Veas-González, Iván; Gomez-Bayona, Ledy; Esponda-Perez, Jorge Alberto; Ezcurra-Zavaleta, Ghenkis; Urraca-Vergara, Elena Matilde (Frontiers in Nutrition, 2025)
IntroductionThis study examines the influence of nutritional literacy on healthy lifestyle behavior and willingness to consume healthy food brands among Peruvian consumers of the Unión brand.MethodsUsing structural equation analysis with data from 637 participants collected between June and September 2023.ResultsThe results confirm that nutritional literacy positively and significantly influences both the willingness to consume healthy brands (β = 0.367, p < 0.001)and healthy lifestyle behavior (β = 0.438, p < 0.001), while the latter also positively impacts the willingness to consume healthy brands (β = 0.220, p < 0.001). Additionally, the mediating effect of healthy lifestyle behavior on the relationship between nutritional literacy and willingness to consume healthy brands is verified (β = 0.096, p < 0.001).DiscussionThese findings demonstrate that improving consumers’ nutritional knowledge not only directly influences their consumption preferences but also enhances this effect through the adoption of healthy habits. This offers relevant implications for marketing strategies focused on nutrition education.